2015
DOI: 10.1016/j.envpol.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of avenue-trees on air quality at the urban neighborhood scale. Part II: Traffic pollutant concentrations at pedestrian level

Abstract: a b s t r a c tFlow and dispersion of traffic-emitted pollutants were studied in a generic urban neighborhood for various avenue-tree layouts by employing 3D steady RANS simulations with the realizable k-ε turbulence model. In comparison to the tree-free situation quantitative and qualitative changes with flow reversal in the wind field were observed. Low to moderate increases (<13.2%) in the neighborhood-averaged pollutant concentration were found at pedestrian level. An approximately 1% increase in the neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(51 citation statements)
references
References 32 publications
1
49
0
1
Order By: Relevance
“…In addition, the fraction of pollutant removed from air by means of the deposition to the leaves is represented as a mass sink in the transport equation (S d , Equation 4). This approach to model vegetation has been evaluated by Santiago et al [24], Krayenhoff et al [37], and Santiago et al [28], and it is also similar to those employed in other CFD studies [23,25,31]. The mathematical expressions are the following,…”
Section: The Study Area and Modeling Set-upmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, the fraction of pollutant removed from air by means of the deposition to the leaves is represented as a mass sink in the transport equation (S d , Equation 4). This approach to model vegetation has been evaluated by Santiago et al [24], Krayenhoff et al [37], and Santiago et al [28], and it is also similar to those employed in other CFD studies [23,25,31]. The mathematical expressions are the following,…”
Section: The Study Area and Modeling Set-upmentioning
confidence: 97%
“…This allows us to generalize the results for different deposition conditions as performed in Santiago et al [25] for idealized scenarios. Specifically, the analysis focuses on:…”
Section: Description Of Investigated Scenariosmentioning
confidence: 99%
“…Several studies have found the presence of trees to cause an increase in levels of both particulate matter and nitrogen dioxide [45,[59][60][61]. The tree canopy may cause pollutants to become trapped by reducing ventilation [45,59,60]. This indicates that the trees have a greater ability to reduce dispersion rates than filter pollutants therefore causing pollutant levels to increase.…”
Section: Impact Of Roadside Vegetationmentioning
confidence: 99%
“…Wind direction and wind speed can be influential on levels of air pollution by increasing or decreasing the rate and area of dispersion [37][38][39][40][41][42][43][44][45][46]. Calm conditions are generally associated with higher levels of air pollution [40,41,43,44,46].…”
Section: Meteorological Impactmentioning
confidence: 99%
See 1 more Smart Citation